1994
DOI: 10.1016/0014-5793(94)00859-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for redox forms of the Aequorea green fluorescent protein

Abstract: Highly purified recombinant Aequorea green fluorescent protein is able to undergo a reversible oxidation-reduction reaction in the presence of molecular oxygen. In the oxidized form in near UV light, the protein is highly fluorescent, but when reduced with sodium dithionite, it becomes completely non-fluorescent. On exposure to molecular oxygen the reduced, non-fluorescent protein reverts to its original fluorescent state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 21 publications
(33 reference statements)
8
84
2
1
Order By: Relevance
“…3). When these samples were further exposed to either dithionite or FeSO 4 , the fluorescence disappeared and then returned upon exposure to air as previously described for the wild type protein exposed to reducing and oxidizing environments [31]. CE experiments were therefore undertaken to determine whether GFP undergoes oxidative/ reductive damage elsewhere on the protein following treatment with O 2 •− .…”
Section: Resultsmentioning
confidence: 99%
“…3). When these samples were further exposed to either dithionite or FeSO 4 , the fluorescence disappeared and then returned upon exposure to air as previously described for the wild type protein exposed to reducing and oxidizing environments [31]. CE experiments were therefore undertaken to determine whether GFP undergoes oxidative/ reductive damage elsewhere on the protein following treatment with O 2 •− .…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism is still unclear, GFP must be modified post-translationally to acquire fluorescent activity. Inouye and Tsuji [22] have reported that the fluorescent intensity of intact dequorea GFP expressed in E. coli cells increases in harvested cells stored overnight at room temperature. Lim et al [23] have also reported the thermosensitive formation of fluorescent GFP in Saccharomyces cerevisiae.…”
Section: Construction and Expression Of Pa-gfpmentioning
confidence: 99%
“…No additive (calcium, a prosthetic group) is necessary for Aequorin to emit light 4,8,9,12,14,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Both groups emit a visible green light in the maximum emission peak (505-509 nm) 14,15,17,18,19,20,21 . The composition of GFP, an 11-stranded β-barrel wrapped around an α-helix, is its most distinctive feature.…”
Section: Introductionmentioning
confidence: 99%